The impact of the COVID-19 pandemic on diagnosis and treatment of patients with soft tissue and bone sarcomas or aggressive benign musculoskeletal diseases: A single-center retrospective study (SarCorD study) - Onesti, Concetta Elisa; Vari, Sabrina; Nardozza, Francesca; Maggi, Gabriella; Minghelli, Denise; Rossi, Barbara; Sperati, Francesca; Checcucci, Elisa; Faltyn, Wioletta; Cercato, Maria Cecilia; Cosimati, Antonella; Biagini, Roberto; et al. (Frontiers in Oncology, 2022)
Background: Covid-19 pandemic led to a rapid reorganization of healthcare activities, leading to reduced access to clinics, interruption of screenings, and treatment schedules modifications in several cancer types. Few data are available on sarcomas. We analyzed Covid-19-related diagnostic delay in a sarcoma referral Center in Italy. Methods: We retrospectively enrolled in this study patients with histological diagnosis of soft tissue or bone sarcoma and aggressive benign musculoskeletal diseases obtained during the first year of the pandemic (Covid group) or the year before (Control group) and followed at Regina Elena National Cancer Institute in Rome. The primary endpoint was the time from the first symptom to histological diagnosis. Results: We evaluated 372 patients, 185 of which were eligible for primary endpoint analysis (92 Control group and 93 Covid group). The patients were affected by soft tissue sarcoma in most cases (63.0% and 67.7% in Covid and Control groups respectively). We observed a diagnostic delay in the Covid group with a median time from the first symptom to the definitive histological diagnosis of 103.00 days (95% CI 92.77–113.23) vs 90.00 days (95% CI 69.49–110.51) in the Control group (p 0.024), but not a delay in treatment beginning (151 days, 95% CI 132.9–169.1 vs 144 days, 95% CI 120.3-167.7 respectively, p 0.208). No differences in stage at diagnosis were observed (12% vs 16.5% of patients with metastatic disease at diagnosis in the Covid and Control respectively, p 0.380). Progression free (p 0.897) and overall survival (p 0.725) were comparable in the subgroup of patients affected by soft tissue sarcoma. Conclusions: A delay in sarcoma diagnosis but not in starting treatment has been observed during the first year of the Covid-19 pandemic. Nevertheless, no difference in stage at diagnosis, nor in terms of survival has been observed.